Comparative transcriptome analysis reveals the signal proteins and defence genes conferring foot rot (Phytophthora capsici sp. nov.) resistance in black pepper (Piper nigrum L.). (December 2019) - Babu Paul, Basil; Mathew, Deepu; Beena, S.; Shylaja, M.R.
Abstract: Foot rot caused by the oomycete Phytophthora capsici is the serious most disease in black pepper, leading to complete crop losses. Even though the cultivars field tolerant to this disease have been identified, molecular mechanisms for the tolerance remain unknown. This study had the objective to identify the candidate genes involved in the foot rot field tolerance of black pepper through comparative transcriptome analysis. P. capsici tolerant/moderately resistant cultivar IISR-Shakthi and susceptible cultivar IISR-Subhakara were artificially inoculated under controlled conditions and mRNAs were isolated from the leaves of treated and control plants at 0, 2, 4, 6, 12, 24, 48 h after inoculation. Transcriptome profiles were compared using DD-RT PCR on cDNA fragments and differentially expressed bands were sequenced. Sequence analysis revealed the involvement of signal proteins and defence enzymes Premnaspirodiene oxygenase, Phosphatase 2C-like domain-containing protein, Nitrous oxide reductase family maturation protein, putative disease resistance protein RGA3, Aspartyl protease, beta-glucosidase enzyme, Cytochrome P450 signal protein, Serine/Threonine Protein kinase WAG1 and nucleoredoxin 1-1 enzyme in field tolerance of black pepper to foot rot. Pathway analysis followed had paved additional insights in to the molecular mechanism of tolerance. Graphical abstract: Image 1 Highlights: Foot rot caused by the oomycete ( Phytophthora capsici sp. nov.) is the most devastating disease of black pepper. Susceptible and tolerant cultivars artificially inoculated, mRNA isolated and first strand cDNA synthesized. Genes amplified using random primers, expression visualised on Urea-PAGE, differentially expressed bands sequenced. Signal proteins and defence enzymes involved in tolerance mechanism identified. Gene expression confirmed through e-Northen and pathways and resistance mechanisms identified.